Improvement of sexuality after hepatitis C cure with direct acting antivirals. (20th October 2020) - Mariño, Zoe; Rodríguez‐Tajes, Sergio; Bartrés, Concepció; Nácar, Loreto; Lens, Sabela; Navinés, Ricard; Cavero, Myriam; Londoño, María C.; Sastre, Lydia; Pocurull, Anna; Dafieno, Angella; Martín‐Santos, Rocío; et al.
Abstract: Despite rarely assessed, sexuality is a relevant domain in Quality of Life. We prospectively evaluated the impact of direct‐acting antiviral therapy on sexuality in a cohort of 186 patients with chronic hepatitis C (HCV). Sexual dysfunction was assessed by validated scales CSFQ‐14/CSFQ‐VAS at baseline and one year after treatment finalization. Median age was 55 years and 87% had mild liver disease. Basal prevalence of sexual dysfunction (62%) and fear of HCV transmission (25%) were high. After HCV cure, both sexual dysfunction prevalence and CSFQ‐VAS improved ( P = .058 and P < .01, respectively), and fear of HCV transmission dropped to 16% ( P = .02). These changes were especially relevant in young men (<55), where sexual dysfunction decreased from 48.6% to 29.7% ( P = .04) and among non‐depressed patients in whom sexual dysfunction decreased from 54.6% to 47% ( P < .01). Age and major depression remained as independent factors of sexual dysfunction persistence after HCV cure. Our data suggest that HCV eradication is associated with an improvement in sexuality, in those patients without depression.